Grip strength values and cut-off points based on over 200, 000 adults of the German National Cohort - a comparison to the EWGSOP2 cut-off points. (23rd January 2023) - Huemer, Marie-Theres; Kluttig, Alexander; Fischer, Beate; Ahrens, Wolfgang; Castell, Stefanie; Ebert, Nina; Gastell, Sylvia; Jöckel, Karl-Heinz; Kaaks, Rudolf; Karch, André; Keil, Thomas; Kemmling, Yvonne; et al.
Abstract: Background: The European Working Group on Sarcopenia in Older People (EWGSOP) updated in 2018 the cut-off points for low grip strength to assess sarcopenia based on pooled data from 12 British studies. Objective: Comparison of the EWGSOP2 cut-off points for low grip strength to those derived from a large German sample. Methods: We assessed the grip strength distribution across age and derived low grip strength cut-off points for men and women (peak mean -2.5 × SD) based on 200, 389 German National Cohort (NAKO) participants aged 19–75 years. In 1, 012 Cooperative Health Research in the Region of Augsburg (KORA)-Age participants aged 65–93 years, we calculated the age-standardised prevalence of low grip strength and time-dependent sensitivity and specificity for all-cause mortality. Results: Grip strength increased in the third and fourth decade of life and declined afterwards. Calculated cut-off points for low grip strength were 29 kg for men and 18 kg for women. In KORA-Age, the age-standardised prevalence of low grip strength was 1.5× higher for NAKO-derived (17.7%) compared to EWGSOP2 (11.7%) cut-off points. NAKO-derived cut-off points yielded a higher sensitivity and lower specificity for all-cause mortality. Conclusions: Cut-off points for low grip strength from German population-based data were 2 kg higher than the EWGSOP2 cut-off points. Higher cut-off points increase the sensitivity, thereby suggesting an intervention for more patients at risk, while other individuals might receive additional diagnostics/treatment without the urgent need. Research on the effectiveness of intervention in patients with low grip strength defined by different cut-off points is needed.